Regional Differences in Early BP Management After Acute Ischemic Stroke in the ENCHANTED International Randomized Controlled Trials - Chen, Chen; Song, Lili; Yang, Jie; Lindley, Richard; Robinson, Thompson; Arima, Hisatomi; Chalmers, John; Anderson, Craig S.; Wang, Xia (Frontiers in Neurology, 2021)
Background and Aims: Epidemiological studies show significant variations in hypertension management within and between countries. The level of regional variation in early blood pressure (BP) management after acute stroke is uncertain. Methods: Data are from the Enhanced Control of Hypertension and Thrombolysis Stroke Study (ENCHANTED), a partial-factorial, international randomized controlled trial of thrombolysis-eligible acute ischemic stroke (AIS) patients with elevated systolic BP (SBP >150 mmHg) assigned to intensive (target SBP 130-140 mmHg) versus guideline-recommended (SBP <180 mmHg) treatment; BP management was compared among four regions: Western countries (Italy/United Kingdom/Spain/Australia), China (mainland), other Asia (Hong Kong/Taiwan/Singapore/Thailand/Vietnam/ India), and South America (Chile/Brazil/Colombia). Results: 2196 AIS (38% women, mean age 67[12] years) patients were included in these analyzes. Commonly used intravenous BP lowering agents were labetalol, nitroglycerin, and topical nitrates in western countries; urapidil, and sodium nitroprusside in China; nicardipine in other Asian countries; and sodium nitroprusside and labetalol in South America. Chinese patients were less likely to receive BP lowering treatment in the first 24 hours and be treated with multiple agents, while they had smaller magnitude of SBP reduction and lower SBP variability. Conclusion: Regional variations in early BP management in acute stroke translated into differences in early BP control parameters.